Catalytic Three‐Component Domino Reaction for the Preparation of Trisubstituted Oxazoles. Issue 24 (16th April 2013) - Wachenfeldt, Henrik v.; Röse, Philipp; Paulsen, Filip; Loganathan, Nagarajan; Strand, Daniel
Abstract Multicomponent reactions are attractive for assembling functionalized heterocyclic compounds. To this end, an efficient gold‐catalyzed three‐component domino reaction to form oxazoles directly from imines, alkynes, and acid chlorides is presented. The reaction proceeds in a single synthetic step by using a gold(III)–N, N′‐ethylenebis(salicylimine) (salen) catalyst to give trisubstituted oxazoles in up to 96 % yield. The substrate scope, a mechanistic study exploring the role of the gold catalyst, and the synthetic applications of the oxazole products are discussed.